Canada : 2021 Article IV Consultation-Press Release and Staff Report. (IMF Staff Country Reports; Country Report, 2021)
The Canadian economy was operating at close to capacity and had strong policy buffers when the COVID-19 pandemic hit. Economic and social restrictions put in place in March 2020 helped to mitigate the first wave of the virus, but they came at a significant cost. There was an unprecedented decline in activity in the first half of 2020, followed by a strong rebound in the third quarter as virus-related restrictions were eased. With the onset of the second wave of the virus in late September sparking renewed restrictions across the country, the recovery has slowed. Looking ahead, the strength and durability of the recovery hinges on the evolution of the pandemic.